Social Relations of The Language Used in The World Statesman Award to President Susilo Bambang Yudhoyono - Mufidah, Anisa; Indah, Rohmani Nur (JEELS (Journal of English Education and Linguistics Studies), 2014)
This study analyzes the written discourse which contains social relation in Tempo newspaper on The World Statesman Award through multidisciplinary Critical Discourse Analysis (CDA) proposed by van Dijk (1998). It concerns with how the discourse of the news has particular purpose in relation to the readers. Employing the theory, this study aims to answer two main questions: (1) What are the social relations of the language use in online Tempo news related to World Statesman Award to President Susilo Bambang Yudhoyono from Appeal of Conscience Foundation2013? (2) How are the social relations of the language use in online Tempo newspaper to World Statesman Award from Appeal of Conscience Foundation 2013? The data analysis covers first, analysis on the context of news followed by drawing semantic macrostructure. Then, identifying the local meaning of the text as well as the social relation is done. The findings show that the social relations reflected in the social cognition of the news cover the knowledge of shared belief, attitude, or shared opinion, and ideology in both shared knowledge and attitude.